Silent cavalry : how Union soldiers from Alabama helped Sherman burn Atlanta--and then got written out of history - Raines, Howell (Crown, 2023)
"A Pulitzer Prize-winning journalist reveals the little-known story of the Union soldiers from Alabama who played a decisive role in the Civil War, and how they were scrubbed from the history books. We all know how the Civil War was won: by courageous Yankees who triumphed over the South. But as veteran journalist Howell Raines shows, it was not only soldiers from Northern states who helped General William Tecumseh Sherman burn Atlanta to the ground, but also an unsung regiment of 2,066 Alabamian yeoman farmers--including at least one member of Raines's own family. Called the First Alabama Cavalry, USA, these 'Mountain Unionists' were the point of the spear that Sherman drove through the heart of the Confederacy. The famed general hailed their skills and courage. So why don't we know anything about them? Silent Cavalry is one part epic American history, one part family saga, and one part scholarly detective story. Drawing on the lore of his native Alabama, and investigative skills honed by six decades in journalism, Raines brings to light a conspiracy that sought to undermine the accomplishments of these renegade Southerners--part of the 'Lost Cause' effort to restore glory to white Southerners after the war, no matter the facts. Raines exposes this tangled web, implicating everyone from a former Confederate general, a gaggle of Lost Cause historians in the Ivy League, and a sanctimonious former keeper of the Alabama State Archives. By reversing the erasure of the First Alabama, Silent Cavalry is a testament to the immense power of historians to destroy, as well as to redeem"--